PENYUSUNAN NORMA PENILAIAN TES KOORDINASI MATA,TANGAN DAN KAKI - Sridadi Sridadi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
Hands-eyes-feet coordination test had been used for the selection of the new students since 2007. Now, thiscoordination test has been widely used by students for the research purposes of the data collection for the finalthesis. Yet, the problem is this coordination test has no standard or norm of judgment. The objective of this researchis to develop the norms or standard of assessment for the hands-eyes-feet coordination test. The research methodwas using survey with test. The population was the students of PJKR and PGSD from the class of 2010 which wasfor about 12 classes. The sampling technique was using a random sampling in which 25% of the class was used toobtain samples of the first class and the second class of PJKR and PGSD with the total of 165 male students and 43female students. The instruments used in the data collection were hands-eyes-feet coordination test which belongedto Sridadi and the reliability of the test was at 0.86. The data obtained were processed and compiled in the formof classification or category. Results of the study illustrate the norm assessment for hands-eyes-feet coordinationtest for the male students in the category of Very Good (48); Good (40-47); Moderate (32-39); Poor (24-3); VeryPoor (23), and for the female students: in the category of Very Good (43); Good (37-42); Moderate (31-36); Poor(25-30); and Very Poor (24).Keywords: Norm Assessment, Hands-eyes-feet coordinationAbstrakTes koordinasi mata tangan dan kaki telah digunakan untuk seleksi calon mahasiswa baru sejak tahun 2007.Saat inites koordinasi tersebut telah banyak digunakan oleh mahasiswa untuk keperluan pengambilan data penelitian dalamrangka tugas akhir skripsi. Permasalahannya tes koordinasi ini sampai saat ini belum ada norma penilaiannya. Tujuanpenelitian ini adalah menyusun norma penilaian tes koordinasi mata tangan dan kaki.Metode dalam penelitian iniadalah survey dengan teknik tes.Populasi penelitian adalah mahasiswa program studi PJKR dan PGSD angkatantahun 2010 berjumlah 12 kelas. Teknik pengambilan sampel menggunakan random sampling yakni 25% dari jumlahkelas sehingga diperoleh sampel 1 kelas PJKR dan 2 kelas PGSD dan berjumlah 165 orang putra dan 43 orangputri.. Instrumen yang digunakan dalam pengambilan data adalah tes koordinasi mata tangan dan kaki milik Sridadiyang memiliki reliabilitas tes 0,86. Data yang diperoleh diolah dan disusun dalam bentuk klasifikasi atau kategori.Hasil penelitian menggambarkan norma penilaian tes koordinasi mata tangan dan kaki untuk putra Baik Sekali (48);Baik (40 – 47); Cukup (32 – 39); Kurang (24 – 3); Kurang Sekali ( 23), dan putriBaik Sekali (43); Baik (37 – 42);Cukup (31 – 36); Kurang (25 – 30); Kurang Sekali ( 24).Kata kunci: Norma Penilaian, Koordinasi mata, tangan, dan kaki